Implementation Of Restorative Justice In The Settlement Of Minute Crimes By The Tulang Bawang Police Criminal Office (Study at Tulang Bawang Police) - Zainab Ompu Jainah; Ahmad Amiruddin S; Oman Ardinata (Cita konsultindo, 2026)
Based on data on minor crimes in Tulang Bawang Regency, it is clear that cases of minor theft, minor assault, and disputes between residents still frequently occur, although the number is relatively small, namely a total of 30 cases in 2025. Of these, most cases were successfully resolved through the application of restorative justice by the Tulang Bawang Police Criminal Investigation Unit, with a total of 21 cases or around 70%. Minor theft cases have the highest resolution rate through RJ, namely 75%, followed by disputes between residents at 70%, and minor assault at 62.5%. This shows that the restorative justice approach is effective in reducing the burden on the courts and law enforcement officers. The formulation of the problem in this study is how is the implementation of restorative justice in resolving minor crimes by the Tulang Bawang Police Criminal Investigation Unit ? and what are the inhibiting factors in the implementation of restorative justice in resolving minor crimes by the Tulang Bawang Police Criminal Investigation Unit ? The research method uses a normative and empirical juridical approach. The types of data used are secondary data and primary data. Data collection was conducted through library research and field research. The data analysis used was qualitative juridical. Based on the research results and discussion, the following conclusions can be drawn: The implementation of restorative justice in resolving minor crimes by the Tulang Bawang Police Criminal Investigation Unit is running well, although not yet optimal. Through penal mediation involving the perpetrator, victim, and family, the settlement is carried out voluntarily and a peaceful agreement is reached. This implementation provides a positive contribution by reducing the caseload and restoring social relations between parties. Inhibiting factors in the implementation of restorative justice in resolving minor crimes by the Tulang Bawang Police Criminal Investigation Unit come from internal and external factors. Internally, limited investigator resources, high workloads, and lack of supporting facilities affect the effectiveness of implementation. Externally, obstacles arise from the unpreparedness of victims or perpetrators to reconcile, third-party intervention, low public understanding, and the uneven dissemination of restorative justice policies. These obstacles mean that the restorative justice process cannot always be applied to all cases. The research suggests that the Tulang Bawang Police Criminal Investigation Unit should improve the quality of restorative justice implementation by strengthening investigator capacity with ongoing training related to penal mediation and empathetic communication. Provision of appropriate mediation space, clear technical guidelines, and regular documentation and evaluation are necessary to ensure a transparent, accountable, and consistent restorative justice process. The Tulang Bawang Police Criminal Investigation Unit should expand the socialization of restorative justice to the community so that victims and perpetrators understand its benefits and mechanisms. Collaboration with community leaders, local governments, and traditional institutions needs to be improved to minimize external obstacles. Strengthening internal coordination is also necessary so that the implementation of restorative justice runs more quickly, effectively, and in accordance with statutory provisions.